First principle investigation of Cr doping effect on the stability of NiFe2O4 - Tianhao Rui; Yulin Lan; Congyi Li; Haibin Zhang; Xiaojing Liu (AIP Advances)
NiFe2O4 is a key component of CRUD (corrosion-related undesirable deposits) that may severely degrade the safety and efficiency of nuclear power systems. Recent experimental studies showed that Cr impurity may affect the formation and growth of NiFe2O4-rich deposit on Cr-coated nuclear fuel, demonstrating a promising solution to inhibit the growth of CRUD. However, little theoretical study has been dedicated to revealing the effect of impurity on the formation and growth of NiFe2O4, especially Cr. In this work, density functional theory was utilized to compute the effect of Cr doping on electronic structures of NiFe2O4. The calculation results suggested that the effect of Cr impurity on NiFe2O4 structural stability is site-dependent and provides theoretical evidence that explains the experimental observation of suppressed NiFe2O4-rich CRUD growth on Cr-coated nuclear fuel. We believe that lattice mismatch induced by Cr doping may lead to stress and dislocations, which suppressed further growth of NiFe2O4. Subsequently, the diffusion of Cr facilitates the smooth growth of the interface, suggesting that the diffusion of Cr may be a crucial factor influencing the growth rate of CRUD.